Leveraging Intellectual Capital And Intellectual Assets: Using Policies and Procedures As Mechanisms to Create Value - Hoo, Wayne E. Soo; Breezee, Jack (Advances in Social Sciences Research Journal, 2020)
This article proposes that Intellectual Capital (CI) is to be considered equivalent to any other asset contributing to the goals and obligations of the organization. To augment CI, Soo Hoo and Beam (2012) developed a writing format for procedures, the workhorse of intellectual assets. This format is designed to meet the information-seeking needs of the employees.